Salicylate-mediated suppression of jasmonate-responsive gene expression in Arabidopsis is targeted downstream of the jasmonate biosynthesis pathway - Leon-Reyes, Antonio (Springer-Verlag, 2010)
Jasmonates (JAs) and salicylic acid (SA) are plant hormones that play pivotal roles in the regulation of induced defenses against microbial pathogens and insect herbivores. Their signaling pathways cross-communicate providing the plant with a regulatory potential to finely tune its defense response to the attacker(s) encountered. In Arabidopsis thaliana, SA strongly antagonizes the jasmonic acid (JA) signaling pathway, resulting in the downregulation of a large set of JA-responsive genes, including the marker genes PDF1.2 and VSP2. Induction of JA-responsive marker gene expression by different JA derivatives was equally sensitive to SA-mediated suppression. Activation of genes encoding key enzymes in the JA biosynthesis pathway, such as LOX2, AOS, AOC2, and OPR3 was also repressed by SA, suggesting that the JA biosynthesis pathway may be a target for SA-mediated antagonism. To test this, we made use of the mutant aos/dde2, which is completely blocked in its ability to produce JAs because of a mutation in the ALLENE OXIDE SYNTHASE gene. Mutant aos/dde2 plants did not express the JA-responsive marker genes PDF1.2 or VSP2 in response to infection with the necrotrophic fungus Alternaria brassicicola or the herbivorous insect Pieris rapae. Bypassing JA biosynthesis by exogenous application of methyl jasmonate (MeJA) rescued this JA-responsive phenotype in aos/dde2. Application of SA suppressed MeJA-induced PDF1.2 expression to the same level in the aos/dde2 mutant as in wild-type Col-0 plants, indicating that SA-mediated suppression of JA-responsive gene expression is targeted at a position downstream of the JA biosynthesis pathway.